Influence of Diffusion-Annealing Temperature on the Physico-Mechanical Properties of Au-doped Bi-2223 Superconductors - Ozturk, O.; Terzioglu, C.; Belenli, I. (Springer Science and Business Media LLC, 2010)
In order to investigate the influence of Au doping and diffusion-annealing temperature on the mechanical and superconducting properties of Bi-2223, Bi1.8Pb0.35Sr1.9Ca2.1Cu3O y superconductors were prepared by standard solid-state reaction methods. Doping of Bi-2223 was carried out by means of gold diffusion during sintering from an evaporated gold film on pellets. The investigation consisted of scanning electron microscopy, dc resistivity and hardness measurements. Electrical-resistivity measurements indicated that the room-temperature resistivity value decreased with decreasing diffusion-annealing temperature from 830 to 500 °C and these samples (G830, G800, G750, G700, G600 and G500) show the resistive behavior above the onset critical transition temperature with the zero-resistivity transition temperatures of 104 K, 80 K, 98 K, 95 K, 102 K and 103 K, respectively. To investigate mechanical properties of the samples, we have measured the diagonal length as a function of test load in the range of 0.245–2.940 N. Mechanical properties (microhardness, Young’s modulus, yield strength and fracture toughness) of the samples are found to be load and diffusion-annealing temperature dependent. In addition, we have calculated the load independent hardness, Young’s modulus, yield strength, and fracture toughness of the samples. The possible reasons for the observed changes in superconducting and mechanical properties due to Au diffusion and diffusion-annealing temperature were discussed.
Keywords: Mechanical Properties of BSCCO; Bi-based Cuprates; Microhardness; Bi-2223; Au Doping